ANALISIS FAKTOR YANG MEMPENGARUHI INDEKS PEMBANGUNAN MANUSIA DI KABUPATEN GORONTALO - Joice Machmud; Desi Saputriyanti Djau (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2019)
This research was conducted at the Gorontalo Regency Central Bureau of Statistics. The purpose of this study was to analyse the dependent variable, the HDI, then the independent variables, namely the health index, education index and per capita expenditure. Data obtained in the form of time series us sourced from the Gorontalo Regency Central Bureau of Statistics (BPS) from 2012-2016. The method used in the study is Multiple Linear Regression. The results of the study are shown by the regression coefficient X1 of 0,719 and the probability value is smaller than 5% which is 0,083 < 0,05, the X2 regression coefficient value is 1.280 and the probability value is smaller than 5% which is 0,035 < 0,05, while the value X3 regression coefficients of 0.001 and probability values smaller than 5% which are 0.181 < 0.05. Each influences the human development index.  Keywords : HDI; Healt; Education Index and Per Capita Expenditure